2000
DOI: 10.1111/j.1749-6632.2000.tb06761.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Gas Hydrates on the Nigerian Continental Slope

Abstract: Gas hydrates were collected in six‐meter piston cores during surface geochemical exploration (SGE) surveys in the deep and ultra deepwaters of Nigeria during 1991, 1996, and 1998. To date, gas hydrates have been collected in about 21 cores out of the more than 800 core collections on the Nigerian margin. This represents a 2.5% recovery ratio of gas hydrated cores on this margin at sites that are potential conduits for the upward migration of hydrocarbons (i.e., the core locations are sited based on two‐ and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…The study area is the continental slope off Nigeria where a large number and variety of surveys have been carried out in recent years as a result of oil and gas industry interest. The continental slope off Nigeria is one of the areas where the occurrence near the seafloor of instability and deformation features have been detected previously by several authors (Damuth, 1994;Cohen and McClay, 1996;Hovland et al, 1997;Brooks et al, 2000;Graue, 2000;Deptuck et al, 2003 among others). This type of shallow feature is of special interest to industrial development because it could become a major risk to any future oil development.…”
Section: Introductionmentioning
confidence: 77%
“…The study area is the continental slope off Nigeria where a large number and variety of surveys have been carried out in recent years as a result of oil and gas industry interest. The continental slope off Nigeria is one of the areas where the occurrence near the seafloor of instability and deformation features have been detected previously by several authors (Damuth, 1994;Cohen and McClay, 1996;Hovland et al, 1997;Brooks et al, 2000;Graue, 2000;Deptuck et al, 2003 among others). This type of shallow feature is of special interest to industrial development because it could become a major risk to any future oil development.…”
Section: Introductionmentioning
confidence: 77%
“…The continental slope off Nigeria is one of the areas where the occurrence near the seafloor of natural gas hydrates has been detected previously by several authors Hovland and Gallagher, 1997;Brooks et al, 2000). This type of gas hydrates accumulation is of special interest to industrial development because they are formed close to the seafloor and possibly could become one of the major risks to any future oil development.…”
Section: Introductionmentioning
confidence: 87%
“…Various studies from the Nigerian continental slope have shown different seafloor sedimentary features such as pockmarks, gas hydrates, slides, mud volcanoes and carbonate build-ups associated with fluid flow (Damuth, 1994;Cohen and McClay, 1996;Hovland et al, 1997;Haskell et al, 1999;Nissen et al, 1999;Brooks et al, 2000;Graue, 2000;Deptuck et al, 2003 amongst others). Heggland (2003) observed gas chimneys above hydrocarbon charged reservoirs.…”
Section: Geological Setting and Seafloor Featuresmentioning
confidence: 95%
“…When gas hydrates are collected in cores they often consist of disseminated nodules of a few centimeters in diameter within the mud matrix a few meters sub-bottom or are massive (5 to 10+ cm thick) and come up as the bottom of the core. The depth of the BSRs are found generally at similar or shallower depths than the calculated base of the methane hydrate stability zone using known bottom water temperatures and thermal gradients for the region 125 .…”
Section: Research In Nigeriamentioning
confidence: 99%
“…All the gas hydrate collections offshore Nigeria to date have been primarily biogenic in nature (methane >99% of the hydrocarbon gases; -60 to -117 0 / 00 ). A few of these gas hydrate sites contain a mixed thermogenic gas component (ethane to butane gases up to a few hundred ppm of total hydrocarbon gas), but even at these sites the primary gas in the hydrates is methane 125 .…”
Section: Research In Nigeriamentioning
confidence: 99%